2017
DOI: 10.5812/asjsm.57690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance and Aerobic Exercise Training or Education Associated with a Dietetic Program on Visfatin Concentrations and Body Composition in Overweight and Obese Women

Abstract: Background: Obesity, as a chronic disease, is becoming increasingly prevalent especially among women. Objectives: The purpose of this study was to evaluate and compare the effects of resistance training (RT), concurrent resistance training and aerobic training (RT + AT) on visfatin concentrations and body composition in overweight and obese women. Methods: An eight-week pretest-posttest design with two experimental exercising groups and one control group was used. 45 overweight and obese women were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Adjustments to the seat height and attachment length depended on the participants' measurements and were based on the guidelines of the isokinetic machine. 4 Before commencing the test, participants completed a 10-minute warm-up session, including the following: walking down the hallway at a fast pace (heart rate <100 beats/min), 27 static and dynamic lower body stretching, and 3 practice trials on the Biodex Isokinetic Dynamometer. The experimental protocol on the Biodex Isokinetic Dynamometer involved participants performing 3 sets of maximum concentric contractions of the quadriceps and hamstring muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustments to the seat height and attachment length depended on the participants' measurements and were based on the guidelines of the isokinetic machine. 4 Before commencing the test, participants completed a 10-minute warm-up session, including the following: walking down the hallway at a fast pace (heart rate <100 beats/min), 27 static and dynamic lower body stretching, and 3 practice trials on the Biodex Isokinetic Dynamometer. The experimental protocol on the Biodex Isokinetic Dynamometer involved participants performing 3 sets of maximum concentric contractions of the quadriceps and hamstring muscles.…”
Section: Discussionmentioning
confidence: 99%
“…It improves glucose tolerance and insulin sensitivity, which are dependent on visfatin concentrations (12). In this regard, Kargarfard et al reported that serum visfatin levels decrease significantly after eight weeks of resistance training and combined aerobic and resistance training (13). Dehghanpisheh et al reported that that the level of plasma visfatin decrease significantly in women following trice weekly training at 60% maximal oxygen uptake (12).…”
Section: Introductionmentioning
confidence: 99%
“…The dietary intervention framework was a balanced meal that included six different types of food. Additionally, a balanced hypocaloric diet (500-1000 kcal wk −1 ) with 25-30 kcal kg −1 , 30-50% fat, 50-60% carbohydrate, and 20-60% protein was prescribed to each participant [28].…”
Section: Caloric Restriction Methodsmentioning
confidence: 99%